Influence of Brand Image and Service Quality on Customer Satisfaction, and Its Impact on Perceived Value of Services, Corporate Image, and Corporate Reputation - Salsabila, Aulia; Kustiawan, Unggul (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study explores the factors that influence customer satisfaction in shopping centers, with a focus on brand image and service quality. These two factors are believed to contribute to customer satisfaction, which in turn shapes the perceived value of services and impacts corporate image and corporate reputation. However, further research is needed to understand this relationship empirically. This quantitative study uses the Structural Equation Modeling (SEM) method, conducted in 2025 with a focus on visitors from 8 shopping centers in Bekasi. Data was collected through an online questionnaire using Google Forms and involved 156 respondents. The analysis process was carried out using the SmartPLS 4 application. The results of the study indicate that brand image and service quality have a positive effect on customer satisfaction. Furthermore, customer satisfaction contributes to an increase in the perceived value of services, which directly impacts the strengthening of corporate image and corporate reputation. These findings provide practical contributions for shopping mall managers in designing strategies to strengthen brand image and improve service quality, thereby creating sustainable customer satisfaction and reinforcing the company's identity and reputation in the eyes of consumers.